Spiritual Festivals as Embodied Sites of Becoming ‘Porous Selves’ - Toomas Gross (Temenos)
Contemporary spiritual festivals attract heterogeneous crowds of adherents of emergent religions, practitioners and aficionados of fringe knowledge, self-seekers, and many others. Focusing on the ethnographic context of Estonia, this paper approaches such festivals as occasions of self-transformation, where festival participants collectively engage in various practices that encourage them to ‘open up’ – to themselves, to others, and to the world. The physical body often takes centre stage in these ritualized activities, which are typically performed in unison and involve interacting with other bodies through synchronized movement and sound, dance, touch, or at the very least deliberate eye contact with others. Charles Taylor’s (2007) distinction between the ‘buffered’ and the ‘porous’ self provides a suitable analytical framework for exploring and understanding these activities’ transformative potential and effect.